Mask Laws to study Texture Features of the Kidney Infection - Hassan, Enass Hammadi; Ali, Alyaa Hussein; Shehab, Russul Mohammad; Mahdi, Mohammed Salih; Abd Alrida, Walaa Ahmad (Iraqi Journal of Science, 2023)
This paper aims to early study of detection and diagnosis of kidney tumors and kidney stones using Computed Tomography Scanning CT scan images by digital image processing. Computerized Axial Tomography (CAT) is a special medical imaging technique that provides images with 3D, including much information about the body’s construction consisting of bones and organs. A C.T scan uses X-rays to create cross-sectional images of the body and gives the doctor a full explanation of the diagnosis of the situation through the examination. It has been used in five cases of kidney images, including healthy, stones, tumors (cancer), cystic and renal fibrosis. The masking procedure is used to separate the required C.T. images from undesirable ones. The segmentation processes which was used in this study is a thresholding algorithm, applied on C.T. images, used to detect unhealthy tissues (tumor and stone). The results showed that the system is able to distinguish between different tumors of the kidney of cases mentioned above. It’s important for the instructor to determine the area of the tumor and stone to avoid damaging the healthy tissue during the treatment. The histogram which was used to study the differences between the healthy and unhealthy depending on the intensity of the image